Efficiency Criteria for Nationalised Industries (Routledge Revivals). - Nove, Alec (Routledge revivals., 2013)
First published in 1973, Efficiency Criteria for Nationalised Industries asks by what criteria we should judge the efficiency of nationalised industries, what we mean by saying they should be run commercially and where the public interest should lie.